7. KNOWLEDGE, PRACTICE FOR PREVENTION OF LOWER GENITAL TRACT INFECTIONS OF WOMEN FROM 18 YEARS OLD AT GIA LAM GENERAL HOSPITAL IN HA NOI PROVINCE IN 2022 AND SOME RELATED FACTORS (Vietnam Journal of Community Medicine, 2023)
Objectives: Assessing the situation, the knowledge and practice of preventing female lower genital tract infections from 18 years old at Gia Lam General Hospital, Hanoi in 2022. Research method: Analytical cross-sectional descriptive study Results: The study subjects had general knowledge obtained about lower genital tract infections and disease prevention, the rate was 51.4%, the knowledge was not reached 48.6%. The rate of general practice obtained on prevention of lower genital tract infections has a low rate of 46.2%, not achieved at 53.8%. The analysis results show a statistically significant relationship p
Keywords: Women, Knowledge-Practice to prevent lower genital tract infections.